Austria's Institutionalized Discriminatory Policies: A Historical Study on Anti-Semitic and Anti-Muslim Phenomena (Departement of Comparative Study of Religions, 2024)
Racism constitutes a serious social issue in Austria. This phenomenon has garnered significant attention from activists, leading to discussions and the formation of numerous organizations dedicated to combating and addressing racism. However, despite decades of anti-racist discourse and efforts in Austria, the issue persists. Reports from anti-racist organizations indicate that incidents of racism remain prevalent to this day. Therefore, it is intriguing to investigate why racism has endured as a dynamic phenomenon in Austria. This article seeks to discuss how politics in Austria institutionalized racism, rooted in a lengthy historical context specifically, racism against the Jewish community (antisemitism) and racism against Muslims. The data were obtained through reviewing previous research findings and reports from anti-racism organizations. Descriptive analysis was employed to provide a detailed explanation of the context within a framework of power relations theory. The study reveals that the ideology inherited from Nazism, which encompasses concepts such as Lebensraum (living space) and the marginalization of specific groups, continues to influence Austrian politics, albeit narrated differently through political campaigns and discriminatory policies. This ideological influence permeates the public sphere, serving as a crucial factor in the unresolved nature of racism in contemporary Austria. Furthermore, the research identifies a shift in political tendencies over time, transitioning from an emphasis on anti-Semitism to Government policies and political campaigns in Austria constitute significant supporting factors influencing racist actions against Muslims in the daily life of Austrian society. wards anti-Muslim racism. Through the perspective of power relations government policies and political campaigns in Austria constitute significant supporting factors influencing racist actions in the daily life of Austrian society. For example, Dokustelle (the Center for Documentation and Counseling on Anti-Muslim Racism in Austria) identified over a thousand cases of racism against Muslims in 2022.